The Relationship between Costing Practices and Benefits : A Case Study of Listed Companies in the Stock Exchange of Thailand - vetchagool, witchulada; Buttarat, Rudchanee (Business Administration and Management Journal Review, 2023)
This study examines the relationship between costing practices and benefits for listed companies on the Stock Exchange of Thailand (SET). The data were collected from 256 companies in three industries, including industrial, consumer products, and services. The research instrument for this survey study was a questionnaire. Sixty-one questionnaires were returned, and they were analysed using descriptive statistics to describe the characteristics of the data. In addition, Pearson correlation was applied to test the association. The findings indicate that the costing practices were intensively used and perceived as highly beneficial by the companies that adopted them, especially variable costing. The study also points out that the companies adopted more than one of these costing practices. The correlation results between all costing practices and benefits show significant relationships (r) with positive signs. This result motivates policymakers and practitioners to focus on formulating strategies to manage activities, resources, and costs through the use of costing practices.